PENGGUNAAN FILM BISU DENGAN TEKNIK DUBBING DALAM PEMBELAJARAN MENULIS DIALOG BAHASA PERANCIS - Yuningsih, Dedeh (2017)
Cette étude vise à décrire l'utilisation du film muet avec le techniaues du doublage dans l'apprentissage de l'ecrire du dialogue en francaise. Le média du film muet peut être trouve facilement. L'utilisation de ce média est facile. Ce média sera utilise simultanement pendant l'apprentissage de la langue francaise.----------This study aims to describe the use of the silent film with the technique of dubbing in the learning of the writing of dialogue in French. The silent film media can be found easily. The use of this medium is easy. This media will be used simultaneously during the learning of the French language. The use of this medium can stimulate the imagination and creativity of learners and make the learning process fun.